Near ultraviolet excited silicate fluorescent powder with excellent luminescence property and preparation method thereof
By preparing near-ultraviolet excitation silicate phosphor, the problem of poor performance of existing luminescent materials is solved, wide spectrum absorption and stable green light emission are achieved, and it is suitable for the anti-counterfeiting field.
Patent Information
- Application Number
- CN202510080632.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2021-10-21
- Publication Date
- 2025-04-29
AI Technical Summary
The existing luminescent materials used for anti-counterfeiting have poor performance, poor luminescent performance, poor temperature and limited application range.
A near-ultraviolet-excited silicate phosphor is used, with a chemical formula of M4-xN6O(SiO4)6:xEu2+, and is prepared by a cation replacement method, with broad spectrum absorption and stable green light emission.
It achieves wide spectrum absorption in the range of 250 to 500 nm, which is suitable for near-ultraviolet-blue light excitation and emits wide spectrum green light emission of 450 to 650 nm. The luminous color is stable and does not change with the ambient temperature.
Smart Images

Figure CN119899667A_ABST
Abstract
Description
[0001] This application is a divisional application. The application number of the parent application is 202111228995.3, the application date is October 21, 2021, and the name of the invention is "A near-ultraviolet excited silicate phosphor, its preparation method and application". Technical Field
[0002] The invention relates to the technical field of luminescent materials, and in particular to a silicate phosphor with excellent luminescent performance and excited by near ultraviolet light, and a preparation method thereof. Background Art
[0003] Various anti-counterfeiting strategies are being continuously developed by researchers. In the past few decades, simple label anti-counterfeiting, plasma technology, magnetic material anti-counterfeiting, holographic anti-counterfeiting technology, etc. have been developed. Among these anti-counterfeiting technologies, luminescent materials are widely used in anti-counterfeiting technology due to their many advantages such as simple design, good visibility, and adjustable colors. In particular, rare earth luminescent anti-counterfeiting technology has aroused the interest of many researchers and received their great attention. Although there are some luminescent materials used in anti-counterfeiting technology, there are still problems such as unsatisfactory luminescent performance, poor temperature resistance, and limited application range. Therefore, it is of great significance to study a luminescent material with ideal performance suitable for the field of anti-counterfeiting. Summary of the invention
[0004] The purpose of the present invention is to provide a near-ultraviolet excited silicate phosphor and a preparation method and application thereof, so as to solve the problem that the existing luminescent materials used for anti-counterfeiting have unsatisfactory performance, so as to provide more choices for the market demand for anti-counterfeiting materials.
[0005] The technical solution of the present invention is: a near-ultraviolet excited silicate phosphor, the chemical formula of which is: M 4-x N6O(SiO4)6:xEu 2+ , wherein M is at least one of Ca, Sr, and Ba, 0.005≤x≤0.6; and N is at least one of Y, La, Gd, and Lu.
[0006] A method for preparing the above-mentioned silicate phosphor comprises the following steps:
[0007] (a) according to the stoichiometric ratio of each element in the chemical formula of the above phosphor, weigh the oxides or carbonates of M, N, Eu and Si as raw materials;
[0008] (b) mixing the weighed raw materials and grinding them uniformly to obtain a mixed powder;
[0009] (c) placing the mixed powder into a corundum crucible, and then placing it in a high-temperature resistance furnace, heating it from room temperature to 1530-1600° C. at a rate of 150-600° C. / h in a carbon reduction or hydrogen reduction atmosphere, and calcining it for 2-10 hours, and then cooling it to room temperature;
[0010] (d) The calcined product is fully ground, washed with ethanol and deionized water, and then dried and sieved to obtain the silicate phosphor.
[0011] In step (b), a flux is added during mixed grinding, wherein the flux is at least one of LiF, NaF, CaF2, SrF2, BaF2, H3BO3, and SiO2, and the flux accounts for 0.5 to 5% of the total mass.
[0012] In steps (b) and (d), the grinding time is 5 to 30 minutes.
[0013] In step (c), the sintering atmosphere is a carbon reducing atmosphere, or a nitrogen-hydrogen mixed gas reducing atmosphere, wherein the hydrogen accounts for 5 to 50%.
[0014] Application of the above-mentioned near-ultraviolet excited silicate phosphor in anti-counterfeiting materials.
[0015] The fluorescent powder provided by the present invention produces wide-spectrum absorption in the range of 250 to 500 nm, is suitable for near-ultraviolet-blue light excitation, and emits wide-spectrum green light emission in the range of 450 to 650 nm, and has a good application prospect.
[0016] The luminescent color of the fluorescent powder provided by the present invention hardly changes with the ambient temperature, that is, the luminescent color of the fluorescent powder in the present invention is relatively stable at different temperatures.
[0017] The present invention uses the method of cation substitution to prepare a phosphor with excitation wavelength dependence, which emits visible light of different wavelengths under different excitations. At the same time, cation substitution changes the structural rigidity, making Eu 3+ The ions cannot be completely reduced, and there is obvious Eu under excitation around 290nm 3+ emission.
[0018] The preparation method of the fluorescent powder of the present invention is simple, the cost is low, and the chemical properties of the prepared fluorescent powder are stable. In addition, since the luminescence thereof has the wavelength-dependent characteristic, the fluorescent powder is suitable for application in the field of fluorescent anti-counterfeiting. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.
[0020] Figure 1 is the XRD diagram of the phosphor prepared in Example 5 of the present invention.
[0021] Figure 2 It is the excitation and emission spectrum diagram of the phosphor prepared in Example 5 of the present invention.
[0022] Figure 3 The emission spectra of the phosphors prepared in Examples 1-5 of the present invention under 292 nm excitation light (y is the content of Sr).
[0023] Figure 4 It is the normalized emission spectrum of the phosphor prepared in Example 5 of the present invention under different excitation wavelengths.
[0024] Figure 5 : This is the CIE chromaticity diagram of the phosphor prepared in Example 5 of the present invention when excited at different wavelengths.
[0025] Figure 6 The anti-counterfeiting pattern designed with the phosphor prepared in Example 5 of the present invention is photographed under natural light, 275nm, 365nm, and 405nm near-ultraviolet light. DETAILED DESCRIPTION
[0026] The present invention is further described below in conjunction with the examples. The processes and methods not described in detail in the following examples are conventional methods well known in the art. Unless otherwise specified, the raw materials or reagents used in the examples are commercially available and can be purchased through commercial channels.
[0027] Example 1: Ba 3.92 La6O(SiO4)6:0.08Eu 2+ Preparation of phosphors.
[0028] a. BaCO3, SrCO3, La2O3, Eu2O3 and SiO2 were weighed as raw materials according to the molar ratio of Ba:La:Si:Eu=1.96:3:3:0.04;
[0029] b. Mix the raw materials weighed in step a and grind them evenly to obtain a mixed powder;
[0030] c. Place the mixed powder in a high-temperature tube furnace, in a N2 / H2 (90% / 10%) atmosphere, and heat from room temperature to 1450°C at a rate of 3°C / min, and maintain for 6 hours. Then cool to room temperature at a rate of 5°C / min;
[0031] d. Grind, wash, dry and sieve the product obtained in step c to obtain Ba 3.92 La6O(SiO4)6:0.08Eu 2+ .
[0032] Example 2: Ba 3.42 Sr 0.5 La6O(SiO4)6:0.08Eu 2+ Preparation of phosphors.
[0033] a. BaCO3, SrCO3, La2O3, Eu2O3 and SiO2 were weighed as raw materials according to the molar ratio of Ba:Sr:La:Si:Eu=3.42:0.5:6:6:0.08;
[0034] b. Add 2 wt% H3BO3 to the raw materials weighed in step a, mix and grind evenly to obtain a mixed powder;
[0035] c. Place the mixed powder in a high-temperature tube furnace, in a N2 / H2 (90% / 10%) atmosphere, and heat from room temperature to 1450°C at a rate of 3°C / min, and maintain for 6 hours. Then cool to room temperature at a rate of 5°C / min;
[0036] d. Grind, wash, dry and sieve the product obtained in step c to obtain Ba 3.42 Sr 0.5 La6O(SiO4)6:0.08Eu 2+ .
[0037] Example 3: Ba 2.42 Sr 1.5 La6O(SiO4)6:0.08Eu 2+ Preparation of phosphors.
[0038] a. BaCO3, SrCO3, La2O3, Eu2O3 and SiO2 were weighed as raw materials according to the molar ratio of Ba:Sr:La:Si:Eu=2.42:1.5:6:6:0.08;
[0039] b. Add 2 wt% H3BO3 to the raw materials weighed in step a, mix and grind evenly to obtain a mixed powder;
[0040] c. Place the mixed powder in a high-temperature tube furnace, in a N2 / H2 (90% / 10%) atmosphere, and heat from room temperature to 1450°C at a rate of 3°C / min, and maintain for 6 hours. Then cool to room temperature at a rate of 5°C / min;
[0041] d. Grind, wash, dry and sieve the product obtained in step c to obtain Ba 2.42 Sr 1.5 La6O(SiO4)6:0.08Eu 2+ .
[0042] Example 4: Ba 1.42 Sr 2.5 La6O(SiO4)6:0.08Eu 2+ Preparation of phosphors.
[0043] a. BaCO3, SrCO3, La2O3, Eu2O3 and SiO2 were weighed as raw materials according to the molar ratio of Ba:Sr:La:Si:Eu=1.42:2.5:6:6:0.08;
[0044] b. Add 2 wt% H3BO3 to the raw materials weighed in step a, mix and grind evenly to obtain a mixed powder;
[0045] c. Place the mixed powder in a high-temperature tube furnace, in a N2 / H2 (90% / 10%) atmosphere, and heat from room temperature to 1450°C at a rate of 3°C / min, and maintain for 6 hours. Then cool to room temperature at a rate of 5°C / min;
[0046] d. Grind, wash, dry and sieve the product obtained in step c to obtain Ba 1.42 Sr 2.5 La6O(SiO4)6:0.08Eu 2+ .
[0047] Example 5: Ba 0.42 Sr 3.5 La6O(SiO4)6:0.08Eu 2+ Preparation of phosphors.
[0048] a. BaCO3, SrCO3, La2O3, Eu2O3 and SiO2 were weighed as raw materials according to the molar ratio of Ba:Sr:La:Si:Eu=0.42:3.5:6:6:0.08;
[0049] b. Add 2 wt% H3BO3 to the raw materials weighed in step a, mix and grind evenly to obtain a mixed powder;
[0050] c. Place the mixed powder in a high-temperature tube furnace, in a N2 / H2 (90% / 10%) atmosphere, and heat from room temperature to 1450°C at a rate of 3°C / min, and maintain for 6 hours. Then cool to room temperature at a rate of 5°C / min;
[0051] d. Grind, wash, dry and sieve the product obtained in step c to obtain Ba 0.42 Sr 3.5 La6O(SiO4)6:0.08Eu 2+ .
[0052] The phosphor prepared in Example 5 was subjected to XRD test, and the results are shown in Figure 1 .pass Figure 1 It can be seen that the prepared Ba 0.42 Sr 3.5 La6O(SiO4)6:0.08Eu 2+ The XRD diffraction peaks of the phosphor are consistent with the data of the standard card PDF#27-0037.
[0053] The fluorescent powder prepared in Example 5 was tested for fluorescence spectrum, and the results are shown in Figure 2 .Depend on Figure 2 It can be seen that the prepared Ba 0.42 Sr 3.5 La6O(SiO4)6:0.08Eu 2+ In phosphor, Eu 2+ 、Eu 3+ The emission coexists, and under the excitation of 292nm light, Eu 3+ Strong emission.
[0054] The luminescence test of the phosphors prepared in Examples 1-5 was performed, and the results are shown in Figure 3 Under 292nm light excitation, as Sr 2+ As the doping concentration increases, Eu 3+ The ion emission gradually increases, and Eu 2+ 、Eu 3+ Emission coexists. When the excitation wavelength is less than 292nm, such as 275nm, it will show a yellow light emission. When irradiated with light around the 375nm band, it will show bright green emission.
[0055] Figure 4 is the normalized emission spectrum of the phosphor prepared in Example 5 under different excitation wavelengths. It can be seen that as the excitation wavelength increases, Eu 3+ The emission gradually weakened and finally disappeared; Eu 2+The emission peak of the phosphor moves toward the long wavelength direction. When the excitation wavelength reaches about 420nm, the emission peak moves to 550nm, showing a yellow emission. As shown in Table 1, the color coordinates of the phosphor luminescence under different excitation wavelengths.
[0056] Table 1: Ba 0.42 Sr 3.5 La6O(SiO4)6:0.08Eu 2+ Color coordinates of phosphors at different excitation wavelengths
[0057]
[0058] Figure 5 : is the CIE chromaticity diagram of the phosphor prepared in Example 5 of the present invention when excited at different wavelengths. It can be seen intuitively that as the excitation wavelength increases, the emission changes from yellow light to green light, and then changes back to yellow light emission. By changing the excitation wavelength, different colors of light can be achieved. Therefore, we designed the following Figure 6 The anti-counterfeiting patterns shown are photos of real objects under natural light, 275nm, 365nm, and 405nm near-ultraviolet light, thereby achieving our goal of realizing the anti-counterfeiting function.
[0059] Example 6: Ba 3.92 La6O(SiO4)6:0.08Eu 2+ Preparation of phosphors.
[0060] a. BaCO3, SrCO3, La2O3, Eu2O3 and SiO2 were weighed as raw materials according to the molar ratio of Ba:La:Si:Eu=1.96:3:3:0.04;
[0061] b. Add 2 wt% H3BO3 to the raw materials weighed in step a, mix and grind evenly to obtain a mixed powder;
[0062] c. Place the mixed powder in a high-temperature tube furnace, in a N2 / H2 (90% / 10%) atmosphere, raise the temperature from room temperature to 1500°C at a rate of 3°C / min, and maintain for 6 hours. Then cool to room temperature at a rate of 5°C / min;
[0063] d. Grind, wash, dry and sieve the product obtained in step c to obtain Ba 3.92 La6O(SiO4)6:0.08Eu 2+ .
[0064] Example 7: Ba 3.92 La6O(SiO4)6:0.08Eu 2+ Preparation of phosphors.
[0065] a. BaCO3, SrCO3, La2O3, Eu2O3 and SiO2 were weighed as raw materials according to the molar ratio of Ba:La:Si:Eu=1.96:3:3:0.04;
[0066] b. Mix the raw materials weighed in step a and grind them evenly to obtain a mixed powder;
[0067] c. Place the mixed powder in a high-temperature tube furnace, in a N2 / H2 (90% / 10%) atmosphere, and heat from room temperature to 1350°C at a rate of 3°C / min, and maintain for 6 hours. Then cool to room temperature at a rate of 5°C / min;
[0068] d. Grind, wash, dry and sieve the product obtained in step c to obtain Ba 3.92 La6O(SiO4)6:0.08Eu 2+ .
[0069] Example 8: Ba 3.92 La6O(SiO4)6:0.08Eu 2+ Preparation of phosphors.
[0070] a. BaCO3, SrCO3, La2O3, Eu2O3 and SiO2 were weighed as raw materials according to the molar ratio of Ba:La:Si:Eu=1.96:3:3:0.04;
[0071] b. Mix the raw materials weighed in step a and grind them evenly to obtain a mixed powder;
[0072] c. Place the mixed powder in a high-temperature tube furnace, in a N2 / H2 (90% / 10%) atmosphere, raise the temperature from room temperature to 1600°C at a rate of 3°C / min, and maintain for 6 hours. Then cool to room temperature at a rate of 5°C / min;
[0073] d. Grind, wash, dry and sieve the product obtained in step c to obtain Ba 3.92 La6O(SiO4)6:0.08Eu 2+ .
[0074] Example 9: Ba 3.995 La6O(SiO4)6:0.005Eu 2+ Preparation of phosphors.
[0075] a. BaCO3, SrCO3, La2O3, Eu2O3 and SiO2 were weighed as raw materials according to the molar ratio of Ba:La:Si:Eu=1.9975:3:3:0.0025;
[0076] b. Mix the raw materials weighed in step a and grind them evenly to obtain a mixed powder;
[0077] c. Place the mixed powder in a high-temperature tube furnace, in a N2 / H2 (90% / 10%) atmosphere, and heat from room temperature to 1450°C at a rate of 3°C / min, and maintain for 6 hours. Then cool to room temperature at a rate of 5°C / min;
[0078] d. Grind, wash, dry and sieve the product obtained in step c to obtain Ba 3.995 La6O(SiO4)6:0.005Eu 2 + .
[0079] Example 10: Ba 3.4 La6O(SiO4)6:0.6Eu 2+ Preparation of phosphors.
[0080] a. BaCO3, SrCO3, La2O3, Eu2O3 and SiO2 were weighed as raw materials according to the molar ratio of Ba:La:Si:Eu=1.7:3:3:0.3;
[0081] b. Mix the raw materials weighed in step a and grind them evenly to obtain a mixed powder;
[0082] c. Place the mixed powder in a high-temperature tube furnace, in a N2 / H2 (90% / 10%) atmosphere, and heat from room temperature to 1450°C at a rate of 3°C / min, and maintain for 6 hours. Then cool to room temperature at a rate of 5°C / min;
[0083] d. Grind, wash, dry and sieve the product obtained in step c to obtain Ba 3.4 La6O(SiO4)6:0.6Eu 2+ .
[0084] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A near-ultraviolet excited silicate phosphor with excellent luminescence performance, characterized in that: Its chemical formula is: Ba 0.42 Sr 3.5 La6O(SiO4)6:0.08Eu 2+ ; The method for preparing the silicate phosphor comprises the following steps: (a) According to the stoichiometric ratio of each element in the chemical formula of the phosphor, weigh the oxides or carbonates of Ba, Sr, Eu and Si as raw materials; (b) mixing the weighed raw materials and grinding them uniformly to obtain a mixed powder; (c) placing the mixed powder into a corundum crucible, and then placing it in a high-temperature resistance furnace, heating it from room temperature to 1450° C. at a rate of 180° C. / h in a carbon reduction or hydrogen reduction atmosphere, and calcining it for 6 hours, and then cooling it to room temperature; (d) grinding the product obtained by calcination thoroughly, washing it with ethanol and deionized water, and then drying and sieving it to obtain the silicate phosphor; The silicate phosphor produces a broad spectrum absorption in the range of 250 to 500 nm, and emits a broad spectrum green light emission in the range of 450 to 650 nm; Adjust Sr 2+ The doping concentration, under 292nm light excitation, increases with the Sr 2+ As the doping concentration increases, Eu 3+ The ion emission gradually increases, Eu 2+ 、Eu 3+ Launch coexistence.
2. A method for preparing the silicate phosphor according to claim 1, characterized in that: The following steps are involved: (a) according to the stoichiometric ratio of each element in the chemical formula of the phosphor of claim 1, weigh the oxides or carbonates of Ba, Sr, Eu and Si as raw materials; (b) mixing the weighed raw materials and grinding them uniformly to obtain a mixed powder; (c) placing the mixed powder into a corundum crucible, and then placing it in a high-temperature resistance furnace, heating it from room temperature to 1450° C. at a rate of 180° C. / h in a carbon reduction or hydrogen reduction atmosphere, and calcining it for 6 hours, and then cooling it to room temperature; (d) The calcined product is fully ground, washed with ethanol and deionized water, and then dried and sieved to obtain the silicate phosphor.
3. The method for preparing silicate phosphor according to claim 2, characterized in that: In step (b), a flux is added during mixing and grinding, wherein the flux is H3BO3 and the flux accounts for 2% of the total mass.
4. The method for preparing silicate phosphor according to claim 2, characterized in that: In steps (b) and (d), the grinding time is 5 to 30 minutes.
5. The method for preparing silicate phosphor according to claim 2, characterized in that: In step (c), the sintering atmosphere is a reducing atmosphere of a nitrogen-hydrogen mixed gas, wherein the hydrogen accounts for 10%.